Factors regarding the dog owner’s household situation, antisocial behaviours, animal views and animal treatment in a population of dogs confiscated after biting humans and/ or other animals - Ineke R. van Herwijnen; Joanne A. M. van der Borg; Chantal M. Kapteijn; Saskia S. Arndt; Claudia M. Vinke (PLoS ONE, 2023)
To examine the dog ownership factors characteristic to a population of dogs confiscated after a human and/ or animal-directed biting incident, we compared bite risk assessment reports of 159 confiscated dogs in the time frame 2008, 2009, 2010 (tf1) and of 215 confiscated dogs in the time frame 2020, 2021, 2022 (until mid-May; tf2). The reports were compiled by the same institute in a standardized format. We studied frequencies and chi-square pairwise comparisons (P<0.05) for 30 identified ownership factors. Overall (tf1 and tf2), 1,308 ownership factors were mentioned in the reports and reports mentioning ≥5 factors were twice as frequent in tf2 (38%) than tf1 (16%). Our data suggest that nine factors may in particular serve as a warning signal for biting incidents, as these factors were most frequently (≥15%) prevalent in the total of reported cases: having a multiple dog household, a dog reportedly roaming a neighbourhood without an owner, a dog’s care tasks being transferred, a short leash and muzzle obligation served to the owner for a dog, an isolated and/ or confined keeping of a dog, a dog owner’s (suspected) substance abuse, a dog owner’s (suspected) animal abuse, a dog owner aggressing at confiscation of the dog and a dog owner being reported on for antisocial behaviours such as intimidation. Particularly, a dog owner’s aggressive or antisocial behaviours and previous obligations to muzzle and short leash a dog (in our dataset often inappropriately adhered to by owners), may indicate that a proportion of owners of confiscated dogs, may not always be willing and/ or capable to guarantee societal safety. The results show that identification of dog ownership factors, might be useful for establishing biting incident policies and further studies should be done on preventive measures and controls.